Detection and prevention of highly pathogenic avian influenza in communities with high poultry disease burdens - Cardona, C.J.; Byarugaba, D.; Mbuthia, P.; Aning, G.; Sourou, S.; Bunn, D.A.; Msoffe, P.L. (Avian Diseases, 2010)
The implementation of strategies to detect, prevent, and control highly pathogenic avian influenza (HPAI) in developing countries presents several challenges, one of which is the presence of other diseases in poultry populations. Training workshops in developing countries using the Avian Flu School have revealed that in areas with heavy Newcastle disease burdens, smallholder poultry keepers do not recognize HPAI as an immediate threat. We have developed a strategy to address the more proximal needs and priorities of communities with free-ranging poultry flocks as a means to create value in poultry, and thus to improve disease detection and prevention overall. To this end, we have created the Poultry Health and Well-Being for Development project, which trains graduate veterinarians and paraprofessionals in poultry disease diagnosis, control, and treatment. These trainees then serve their local communities to improve poultry health and to implement disease detection and management programs. © 2010 American Association of Avian Pathologists.
Keywords: Avian influenza; Newcastle disease; Poultry health; Village poultry